Comparison Between L-312 Hydrophobic-Hydrophilic Acrylate and US-860 UV Hydrophilic Acrylate IOL Opacification Characteristic - Xie, Jin; Sun, Jie; Liu, Ting; Mao, Shilan; Dai, Yunhai (Frontiers in Medicine, 2022)
Objective: To compare opacity characteristics of US-860UV and L-312 IOL, and report the phenomenon of glistenings in hydrophobic-hydrophilic acrylic IOLs Setting: Qingdao Eye Hospital Design: Experimental study Methods: Four medical records (4 eyes) of patients with L-312 or US-860UV IOL opacification reporting decreased or lost vision who underwent IOL explantation between 2019 and 2021 were reviewed. Explanted IOLs were analyzed by slit-lamp examination, confocal microscopy, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS) at Qingdao Eye Hospital and Qingdao university of science and technology. Results: The 4 explanted IOLs were represented by 2 hydrophilic acrylic designs. The preoperative mean corrected distance visual acuity changed from 1.84±1.09 logarithm of the minimum angle of resolution (log MAR) to 0.20±0.03 log MAR postoperatively (P < .001) except case 3. The mean interval of the L-312 IOL was 56.67±14.19 months (range 44 to 72 months), and the interval of the US-860UV IOL was 27 months. Morphological findings were surface, subsurface calcifications of the US-860UV IOL material, and the optical region of L-312 IOLs are teeming with a great number of vacuoles by light microscope, scanning electron microscope, and Energy Dispersive X-ray Spectral. Conclusion: The cause of US-860UV opacification was primary calcification, and vacuoles resulted in L-312 IOL opacification.